yeast transcription factor genes YAP1 and YAP2 are subject to differential control at the levels of both translation and mRNA stability - Vilela, C; Linz, B; Rodrigues-Pousada, C; McCarthy, J.E.G (Nucleic acids research, 1998)
Two forms of post-transcriptional control direct differential expression of the Saccharomyces cerevisiae genes encoding the AP1-like transcription factors Yap1p and Yap2p. The mRNAs of these genes contain respectively one (YAP1 uORF) and two (YAP2 uORF1 and uORF2) upstream open reading frames. uORF-mediated modulation of post-termination events on the 5′-untranslated region (5′-UTR) directs differential control not only of translation but also of mRNA decay. Translational control is defined by two types of uORF function. The YAP1-type uORF allows scanning 40S subunits to proceed via leaky scanning and re-initiation to the major ORF, whereas the YAP2-type acts to block ribosomal scanning by promoting efficient termination. At the same time, the YAP2 uORFs define a new type of mRNA destabilizing element. Both post-termination ribosome scanning behaviour and mRNA decay are influenced by the coding sequence and mRNA context of the respective uORFs, including downstream elements. Our data indicate that release of posttermination ribosomes promotes largely upf-independent accelerated decay. It follows that translational termination on the 5′-UTR of a mature, non-aberrant yeast mRNA can trigger destabilization via a different pathway to that used to rid the cell of mRNAs containing premature stop codons. This route of control of non-aberrant mRNA decay influences the stress response in yeast. It is also potentially relevant to expression of the sizable number of eukaryotic mRNAs that are now recognized to contain uORFs.